Comparative Study of Problem Based Learning and Jigsaw Models in Enhancing Students’ Critical Thinking Skills in Islamic Religious Education - Cahyani, Heni; Eliva Sukma Cipta; Hoerul Umam (Journal of Teacher Training and Educational Research, 2025)
Critical thinking is an essential skill for students in the 21st century, enabling them to analyze, evaluate, and make rational decisions. However, students’ critical thinking in Islamic Religious Education (IRE) often remains low, as learning tends to emphasize memorization rather than analytical skills. This study aims to (1) describe students’ critical thinking skills when taught using the Problem Based Learning (PBL) model, (2) describe students’ critical thinking skills when taught using the Jigsaw cooperative model, and (3) compare the differences between the two approaches. The research employed a quantitative quasi-experimental design with a posttest only non-equivalent control group. The participants were 22 tenth-grade students of SMKN 10 Bandung, divided into two classes: 11 students in the experimental group (PBL) and 11 students in the control group (Jigsaw). Data were collected through a critical thinking test adapted from Ennis’ indicators and analyzed using descriptive statistics and an independent samples t-test. The results revealed that students taught with PBL achieved a higher mean score (M = 76.36, SD = 5.52) than those taught with Jigsaw (M = 61.82, SD = 13.83). The t-test indicated a significant difference between the two groups (t = 2.683, p < 0.05). The findings suggest that PBL is more effective in fostering students’ critical thinking compared to Jigsaw, as it engages learners in real-life problem solving and analytical reasoning.